Implications of The Imposition of Duties on The Acquisition of Land and Building Rights to Land Ownership in Indonesia - Sri Karyati (TAFAQQUH, 2021)
This research aims to examine the juridical implications of tax imposition in the acquisition of land and building rights to land ownership in Indonesia. Taxes related to land in Indonesia are on Earth and Building Tax (UN) and Land and Building Rights Acquisition Duty. But in the implementation of BPHTB problems often arise related to data collection, BPHTB object assessment method, calculation of the amount of taxes owed. In BPHTB the amount of tax calculated if associated with a self-assessment system where the taxpayer who determines the amount of tax owed and pay it themselves raises the possibility of greater tax avoidance. The authors concluded that the imposition of BPHTB The acquisition of land and building rights until now has not had effective implications for land ownership in Indonesia, because the reality on the land of one taxpayer can have the right to land and buildings more than one and has not had implications for the utilization in accordance with the spatial and land use. So according to the author, changes were made to the determination of BPHTB tariffs based on the region or area where the acquisition of land and building rights was obtained by paying attention to spatial and land use.